3D Numerical Simulation of Heat Transfer of a Heated Plate under the Electric Field Generated by a Needle Electrode. (25th September 2014) - Zhang, Jianfei; Zhao, Chu; Li, Hongyan; Tao, Wenquan
Abstract : A three-dimensional numerical model that couples the electric field, velocity field, and temperature field is developed based on the commercial code COMSOL Multiphysics. The influences of several factors on convective heat transfer on a heated plate in the electric field generated by a needle electrode are observed. The factors are the applied voltage, the distance between the two electrodes, and the size of the ground plate. The results show that applied voltage is one of the most important factors for the convection heat transfer. The convection heat transfer efficiency significantly increases with the improvement of the applied voltage. From the perspective of the model size, the decrease of the distance between two electrodes and the size of the plate could improve the average convection heat transfer coefficient. Smaller ionic wind device needs lower applied voltage and less electric energy to obtain the same average convection heat transfer coefficient as the bigger one, which provides the theoretical basis for the potential of miniaturizing the ionic wind cooling device.